Technologies and strategies for aflatoxin control in Ghana: A synthesis of emerging evidence - Hoffmann, Vivian; Grace, Delia; Lindahl, Johanna F.; Mutua, Florence K.; Ortega Beltran, A.; Bandyopadhyay, Ranajit; Mutegi, C.; Herrman, T. (International Food Policy Research Institute, 2019)
Aflatoxin is a poisonous substance produced by a fungus, Aspergillus flavus, that occurs naturally in soils of cultivated and non-cultivated areas. The fungus commonly produces the toxin in maize, groundnut, and other staple grains and vegetables, and is especially prevalent in Africa. When animals consume feed contaminated with aflatoxin, milk and (at very low levels) meat, fish and eggs, can also be contam-inated. This note brings together recent research from the CGIAR and others on technologies for aflatoxin control in Africa and provides recommendations for catalyzing their adoption.